A deep eutectic solvent strategy to form defect-rich N, S, and O tridoped carbon/Co9S8 hybrid materials for a pH-universal hydrogen evolution reaction. Issue 4 (20th January 2021) - Mou, Hongyu; Xue, Zhimin; Zhang, Baolong; Lan, Xue; Mu, Tiancheng
Abstract : This ultrathin structure can be attributed to the decomposition of thiourea in the DES during the pyrolysis process, a large amount of gas (such as NH3, CO2, etc. ) to strip the product. Abstract : In this work, we proposed a new strategy to form a defect-rich ultra-thin N, S, and O tridoped carbon/Co9 S8 (NSOC/CS) composite by coating a deep eutectic solvent (DES) on carbon cloth and calcining. The composition, structure, and electrochemical performance of NSOC/CS can be rationally designed by the choice of DES. Density functional theory (DFT) calculations and experimental results show that NSOC/CS has the optimized adsorption energy of H2 O (Δ G H2 O* ) and hydrogen (Δ G H* ). Electrochemical tests show that NSOC/CS has excellent hydrogen evolution reaction (HER) activity. In 1.0 M KOH, 1.0 M PBS, and 0.5 M H2 SO4 electrolytes, only 53, 103, and 68 mV overpotentials are required to reach a current density of 10 mA cm −2, and the composite exhibits excellent stability and durability at all pH values. DFT results show that N doping is beneficial to the hydrogen evolution reaction of the catalyst in neutral and alkaline electrolytes, and doping S atoms is beneficial to the hydrogen evolution reaction of the catalyst in acidic electrolytes. This work provides a facile and green route to form heteroatom-doped carbon/metal sulfide hybrid materials with high catalytic HER activity.